Interaction of human osteoblast-like Saos-2 cells with stainless steel coated by silicalite-1 films - Jirka, Ivan; Vandrovcová, Marta; Plšek, Jan; Bouša, Milan; Brabec, Libor; Dragounová, Helena; Bačáková, Lucie (Materials science & engineering. C, Materials for biological applications, 2017)
This paper investigates the interaction of human osteoblast-like Saos-2 cells with stainless steel covered by a film of densely inter-grown silicalite-1 crystals with defined outer and inner surfaces. The chemical composition of this film, labeled as SF(RT), was tuned by heat treatment at 300°C and 500°C (labeled as SF(300) and SF(500), respectively) and characterized by X-ray photoelectron spectroscopy (XPS), water drop contact angle (WCA) measurements and scanning electron microscopy (SEM). The number, the spreading area and the activity of alkaline phosphatase of human osteoblast-like Saos-2 cells in cultures on the silicalite-1 film were affected by the chemical composition of its outer surface and by its micro-porous structure. The number and the spreading area of the adhered osteoblast-like cells on day 1 was highest on the surface of SF(RT) relative to their adhesion and spreading on a glass cover slip due to the SF(RT) topology. However, SF(300) markedly supported cell growth during days 3 and 7 after seeding.
Keywords: Humans; povrchové vlastnosti; Photoelectron Spectroscopy; fotoelektronová spektroskopie; osteoblasty; Silicon Dioxide; nerezavějící ocel; Microscopy, Electron, Scanning; Cell Adhesion; lidé; Osteoblasts; buněčné linie; Biocompatibility; Cell Line; mikroskopie elektronová rastrovací; Stainless Steel; oxid křemičitý; Silicalite-1 film; buněčná adheze; Surface Properties; Human osteoblast-like Saos-2 cells